Effect of the strong coupling on the exchange bias field in IrMn/Py/Ru/Co spin valves - Tarazona H.S. (2018)
This work has been partially supported by the Brazilian agencies CNPq and CAPES. H.S.T. thanks to the Peruvian Doctoral Scholarship of CIENCIACTIVA (CONCYTEC) under Grant #218-2014-FONDECYT. C.V.L. and J.Q-M are grateful to CIENCIACTIVA (CONCYTEC) for financial support throught the Excellence Center Programs. We also acknowledge E.B. Saitovitch and CBPF for experimental facilities.